Exploring Theological and Biblical perspectives on wealth and poverty - Boaheng, Isaac; Boateng, Alexander Kwasi; Boaheng, Samuel (Universitas PGRI Madiun, 2024)
The subject of wealth and poverty is one of the major themes in the JudeoChristian Scriptures. The continent of Africa is one of the regions hugely affected by poverty. As such, there is an ongoing discourse about the biblical view of wealth and how it may be used in tackling the canker of poverty. At one breath, our contemporary materialistic culture is seducing Christians to accept the idea that poverty is a curse from God, whilst on the other extreme, wealth is viewed as an impediment to entering the kingdom of God. While a complete eradication of poverty remains a formidable challenge, particularly in vulnerable contexts, there exists an opportunity for more concerted efforts to alleviate the plight of the impoverished. As a contribution to the scholarly discourse, this paper examined what the Bible reveals about wealth and poverty and made relevant theological deductions for African church in dealing with wealth and poverty. This is timely against the backdrop that the “centre of gravity” of Christianity is in Africa which makes it befitting to address the menace of poverty from the biblical standpoint. The paper conducted a theological study of relevant biblical passages. The fact that one’s wealth does not necessarily indicate their acceptance by God and the need to share material resources were emphasized. Though the authors had the African continent in mind, the paper also applies to other contexts which share Africa’s socio-economic realities.